Effect of low voltage electric currents on the decrease of Klebsiella pneumoniae ESBL and non-ESBL colonies - Setya Wijoyo, Dhia Lintang; Koendhori, Eko Budi; Susilo, Imam; Wardhani, Puspa (Indonesian Society for Clinical Microbiology (Perhimpunan Dokter Spesialis Mikrobiologi Klinik Indonesia), 2023)
Introduction: Klebsiella pneumoniae is a gram-negative bacteria and one of the most common causes of nosocomial infections, especially in the intensive care units. The use of liberal and irrational antibiotics is shown the emergence of antibiotic-resistant Klebsiella pneumoniae. This research was conducted to evaluate if low voltage electric current on three kinds of solvent media could have an eradication effect. Methods: This was an experimental study, which was done at the Microbiology Laboratory of Harapan Kita Women and Children Hospital-Jakarta. This study used to isolate bacteria non-ESBL and ESBL Klebsiella pneumoniae, thereupon will be dissolved in saline, Aqua destillata, and Ringer Lactate, each consisting of 8 samples. Each sample received a 0.5V and 10mA DC electric current; reduction of colonies was observed at 30, 60, 120 and 240 minutes using DensiCHEK. Result: There was a decrease in the colony number of 2 bacterial groups in the first 30 minutes in all three media (p <0.01). The reduction was higher in the non-ESBL K. pneumoniae group. The decrease of bacterial colonies was higher in the Klebsiella pneumoniae group non ESBL in ringer lactate medium during 240 minutes observation compared to saline and Aqua destillata (p <0.001; p <0.001, respectively). The saline solution showed no different effect compared to aquadestillata. Conclusion: A direct current of 10 mA and 0.5 V intervention, on Ringer lactate media, could have a bacterial killing effect to Klebsiella pneumoniae non ESBL started from 30 minutes. Klebsiella pneumoniae ESBL needed a longer duration than non ESBL.